Long-term effects of biochar application on the growth and physiological characteristics of maize - Cong, Mengfei; Hu, Yang; Sun, Xia; Yan, Han; Yu, Guangling; Tang, Guangmu; Chen, Shuhuang; Xu, Wanli; Jia, Hongtao (Frontiers in Plant Science, 2023)
Biochar, as a soil conditioner, has been widely used to promote the growth of maize, but most of the current research is short-term experiments, which limits the research on the long-term effects of biochar. In particular, the physiological mechanism of biochar on maize growth in aeolian sandy soil is still unclear. Therefore, we set up two groups of pot experiments, respectively after the new biochar application and one-time biochar application seven years ago (CK: 0 t ha-1, C1: 15.75 t ha-1, C2: 31.50 t ha-1, C3: 63.00 t ha-1, C4: 126.00 t ha-1) to explore the effect of biochar on maize growth physiology and its after-effect. Results showed that the plant height, biomass, and yield of maize showed the highest rates of increase at the application rate of 31.50 t ha-1 biochar, with 22.22% increase in biomass and 8.46% increase in yield compared with control under the new application treatment. Meanwhile, the plant height and biomass of maize increased gradually with the increase of biochar application under the one-time biochar application seven years ago treatment (increased by 4.13%-14.91% and 13.83%-58.39% compared with control). Interestingly, the changes in SPAD value (leaf greenness), soluble sugar and soluble protein contents in maize leaves corresponded with the trend of maize growth. Conversely, the changes of malondialdehyde (MDA), proline (PRO), catalase (CAT), peroxidase (POD) and superoxide dismutase (SOD) manifested an opposite trend to the growth of maize. In conclusion, 31.50 t ha-1 biochar application can promote the growth of maize by inducing changes in its physiological and biochemical characteristics, but excessive biochar application rates ranging from 63.00-126.00 t ha-1 inhibited the growth of maize. After seven years of field aging, the inhibitory effect of 63.00-126.00 t ha-1 biochar amount on maize growth disappeared and changed to promoting effect.